Determination of Consumer Unit Scales - Singh, Balvir; Nagar, A. L. (Econometrica, 1973)
[This paper develops an iterative procedure for estimating "specific" and "income" consumer unit scales in Engel curve analysis. The proposed procedure is essentially a modification of the Prais and Houthakker method and is illustrated by means of a numerical example based on the Indian National Sample Survey data.]